Islamic Finance in Academia: Investigating Hybrid Sukuk Model (Ijarah-based Diminishing Musharaka) Implementation in KP’s Government Universities - Muhammad Arsalan Akbar; Dr. Qaisar Bilal; Dr. Muhammad Kaleem (Dialogue Social Science Review (DSSR), 2025)
Higher education institutions including Pakistan face the problem of inadequate funds due to financial challenges and increasing costs, ensuring innovative techniques for financial sustainability. The rising demad for such tools has lead universities to exploration of creative solutions like hybrid sukuk . The purpose of the current study is to explore the prospects and challenges of ijarah-based diminishing musharakasukuk financing model in the public sector universities. The methodology involves the data collection technique which is semi-structured interviews with stake holders like financial experts of Islamic bankers, Islamic scholars teaching Islamic financing and have a extensive knowledge regarding sukuk and universities administration like assistant treasurer and deputy auditor. The data analysis technique used is reflexive thematic analysis for insights into the prospects and challenges vis-à-vis the financing model.The multidimensional aspects of the ijarah-based diminishing musharaka model with respect to its prospects and challenges encompass compliance of shariah, social responsibility, mutual benefits along with operational aspects. To fully realize the prospects of sukuk with regards to legal challenges, awareness and risk management and to address the resistance towards change impacting investor’s confidence, proactive communication and education efforts are considered necessary and moreover further developments with respect to research and collaborative efforts are ensured to dispel the misconceptions regarding Islamic financing models and to adopt sukuk as a viable and practical solution in higher education sector